TEACHING READING COMPREHENSION DESCRIPTIVE TEXT BY USING PRE-QUESTIONING TECHNIQUE TO THE THIRD SEMESTER OF ENGLISH EDUCATION DEPARTMENT AT UNIVERSITAS ISLAM LAMONGAN - Riya Risqi Setyaningrum (Universitas Islam Lamongan, 2018)
One of the important skills that should be mastered in foreign language is reading. In teaching reading activity in the classroom, sometimes students get difficulty in comprehending the text. They could not comprehend the text well that is caused by some factor. One of the factors is lack of information. Pre-questioning is one of the techniques in teaching reading which can give an interaction between the teacher and the students to read the text. The purpose of pre-questioning is to build students’ interest and motivation. This study was conducted by the implementation of pre-questioning technique to teach reading comprehension descriptive text. The population was the students’ of English Education Department at Universitas Islam Lamongan. The sample was the students of first semester. The class consisted of 30 students. Pre-questioning technique used some tests; each test was different items of questions. The data was taken by observation checklist and tests. The measure of the students’ achievement was stated by Harris (1969:134). The data have got from the result of pre-test, formative test1, formative test 2 and post-test. It found that post-test is higher than pre-test and formative test. The percentages were added from pre-test 56.67% to post-test 80%. In conclusion, pre-questioning gives the contribution towards students’ reading comprehension ability. After conducting the study, the researcher suggests that in teaching reading, the English teacher should build a favorable atmosphere at times of teaching-learning process conducted, because a conductive condition in teaching would become one way to carry out the material to be taught and improve the students’ interest and motivation in learning English, especially in reading skill. Key words: Reading Comprehension, Teaching Reading, Pre-Questioning Technique, Descriptive Text